Improving heat use efficiency of wheat (Triticumaestivum L.) under abiotic stresses in semi-arid and arid agroclimatic conditions of Punjab - SINGH, HARKANWALJOT; KINGRA, P. K.; PAL, R. K.; SINGH, SOMPAL (MAUSAM, 2021)
A field experiment was conducted in two agroclimatic zones of the Punjab (viz., Ludhiana representing semi-arid and Bathinda representing arid zone) to study the phenologicalbehaviour and heat use efficiency of wheat under abiotic stresses. The wheat variety HD-2967 was evaluated under five thermal environments (D1- 20th October, D2-5th November, D3- 20th November, D4- 5th December and D5- 20th December) to expose the crop to different thermal environments and two nitrogen levels (N1- Recommended dose of N and N2- 25 per cent less than recommended N) in main plots and two irrigation levels (I1 - Optimal (recommended) irrigation (Irrigation at CRI, Jointing, Flowering and Soft dough stage) and I2 - Sub-optimal irrigation (one irrigation less than recommended) (Irrigation at CRI, Flag leaf emergence and Soft dough stage) in sub-plots during two consecutive rabi seasons of 2017-18 and 2018-19. It was found that the wheat crop sown in semi-arid zone i.e., Ludhiana took more number of days to reach physiological maturity. The number of days required to attain different phenological stages decreased with delayed sowing at both the locations. The crop utilized heat more efficiently in the arid zone i.e., Bathinda. At Ludhiana, highest HUE was observed in the crop sown on 20th November (3.08 kg/ha/°C/day) and 5th November (3.18 kg/ha/°C/day) during 2017-18 and 2018-19, respectively; whereas at Bathinda, HUE was highest in the crop sown on 5th November (3.31 and 3.32 kg/ha/°C/day) during both the years. Recommended dose of nitrogen and optimal irrigation also produced significantly higher HUE at both the locations during both the years. The study concluded that timely sowing of the crop along with recommended nitrogen and optimal irrigation can significantly improve efficiency of heat utilisation both in semi-arid and arid agroclimatic conditions.